Growth of Black TiO2 Quantum Dots by Solution‐Based Electrochemical Process. Issue 1 (2nd September 2020) - Saranrom, Natpapon; Sintiam, Thanakrit; Panyathip, Rangsan; Hongsith, Kritsada; Sucharitakul, Sukrit; Ngamjarurojana, Athipong; Boonyawan, Dheerawan; Kumnorkaew, Pisist; Kerdcharoen, Teerakiat; Choopun, Supab
Abstract : Black titanium dioxide (TiO2 ) quantum dots (QDs) are grown by a solution‐based electrochemical process and an effect of KCl concentration on the growth is investigated. The electrochemical process is demonstrated as a simple one‐step process for the growth of black TiO2 QDs in the solutions via bottom–up process. From the absorption spectra, the absorption appears for an entire visible wavelength (400–700 nm) implying a black TiO2 property. The average size of the black TiO2 QDs is about 4.5 nm from the transmission electron microscopy results and is similar to all KCl concentrations. This indicates that KCl concentration has no effect on the particle size, but has effect on the hydrodynamic size of TiO2 QDs. The black TiO2 QDs can be produced by the hydrogenation process of hydrogen ions during electrochemical process. The obtained black TiO2 QDs can be further explored as an electron‐transporting layer for a perovskite solar cell application. Abstract : The black titanium dioxide (TiO2 ) quantum dots (QDs) are successfully grown by a solution‐based electrochemical process. The black TiO2 QDs show broader absorption over a visible range (400–700 nm). Transmission electron microscopy indicates that average size of the black TiO2 QDs is 4.5 nm. The obtained black TiO2 QDs can be further explored as an electron‐transporting layer for perovskite solar cell application.